Theoretical and Methodological Context of (Post)-Modern Econometrics and Competing Philosophical Discourses for Policy Prescription - Emerson Abraham Jackson (Ludwig-Maximilians-Universität (LMU), 2018)
This research article was championed as a way of providing discourses pertaining to the concept of "Critical Realism (CR)" approach, which is amongst many othe forms of competing postmodern philosophical concepts for the engagement of dialogical discourses in the area of established econometric methodologies for effective policy prescription in the economic science discipline. On the the whole, there is no doubt surrounding the value of empirical endeavours in econometrics to address real world economic problems, but equally so, the heavy weighted use and reliance on mathematical contents as a way of justifying its scientific base seemed to be loosing traction of the intended focus of economics when it comes to confronting real world problems in the domain of social interaction. In this vein, the construction of mixed methods discourse(s), which favour that of CR philosophy is hereby suggested in this article as a way forward in confronting with issues raised by critics of mainstream economics and other professionals in the postmodern era. – – Cet article de recherche a été présenté comme un moyen de fournir des discours sur le concept de «Réalisme critique (CR)», parmi de nombreuses autres formes de concepts philosophiques postmodernes concurrents pour l'engagement de discours dialogiques dans le domaine des méthodologies économétriques établies. prescription politique efficace dans la discipline des sciences économiques. Dans l'ensemble, il n'y a aucun doute sur la valeur des efforts empiriques en économétrie pour résoudre les problèmes économiques du monde réel, mais de même, l'utilisation pondérée et le recours aux contenus mathématiques comme moyen de justifier sa base scientifique semblent perdre de l'intention de l'économie quand il s'agit de faire face aux problèmes du monde réel dans le domaine de l'interaction sociale. Dans cet esprit, la construction de discours sur les méthodes mixtes, qui favorisent celle de la philosophie CR, est suggérée dans cet article comme une voie à suivre face aux problèmes soulevés par les critiques de l'économie dominante et d'autres professionnels de l'ère postmoderne.
Additional information: This is a forthcoming article which will be published by the Postmodern Openings Journal in Vol. 9, Issue 3 (September, 2018).
Keywords: A12; B50; C18; 330; Theoretical; Methodological Intervention; Critical Realism; Postmodern; Econometrics